PERSEPSI MASYARAKAT TANGKENO TERHADAP DESA WISATA - Hardiansyah Hardiansyah; Syamsumarlin Syamsumarlin; Akhmad Marhadi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
The purpose of this study is to find out the perceptions of local people about the existence of tourist destinations and the impact that people have on the existence of tourist villages. The theory used is the theory of phenomenology Eddmund Husserl. This research is qualitative descriptive research and data collection is done through observation (observation) and interviews. The results of the study show that the existence of the Tangkeno tourist village raises various perceptions and from various community groups. Such a phenomenon can be seen in the perceptions of the government, traditional leaders, community leaders, religious leaders, youth leaders, and students. Some positive impacts experienced by local communities, among others: improving the economy of the community and the region, improving the values ​​of local culture, gaining new knowledge and experience. Nevertheless, negative impacts also arise such as creating new cultures and employment competition.